2019
DOI: 10.5039/agraria.v14i3a5659
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização do carvão vegetal produzido em fornos retangulares industriais

Abstract: RESUMO: O objetivo deste estudo foi caracterizar as propriedades do carvão vegetal produzido em fornos retangulares industriais, por meio da análise de componentes principais. Para isto, foram amostrados três estoques industriais de carvão vegetal, provenientes dos Forno I e II, com capacidade volumétrica de 500 e 180m 3 de madeira, respectivamente. Determinaramse as características do carvão vegetal, como granulometria média, teor de finos, densidade a granel e composição química imediata. Foram realizadas as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
(15 reference statements)
1
5
1
Order By: Relevance
“…The produced wood charcoal had an average fixed carbon value equal to 75.39%, and this value was close to that verified by Arruda et al (2011) and Figueiró et al (2019), who evaluated the quality of eucalyptus charcoal produced in rectangular kilns with temperature control. The fixed carbon value found was adequate, as the average percentage for using charcoal as an input for the steel industry should vary between 70 and 75% fixed carbon (Carneiro et al, 2013;Santos et al 2016).…”
Section: /8supporting
confidence: 88%
See 4 more Smart Citations
“…The produced wood charcoal had an average fixed carbon value equal to 75.39%, and this value was close to that verified by Arruda et al (2011) and Figueiró et al (2019), who evaluated the quality of eucalyptus charcoal produced in rectangular kilns with temperature control. The fixed carbon value found was adequate, as the average percentage for using charcoal as an input for the steel industry should vary between 70 and 75% fixed carbon (Carneiro et al, 2013;Santos et al 2016).…”
Section: /8supporting
confidence: 88%
“…The average bulk density of charcoal in this study (Table 2) was higher than that observed by Figueiró et al (2019), who found average values ranging from 180 to 205 kg m -3 when characterizing the charcoal properties produced in rectangular industrial kilns. However, this difference can be attributed to the difference in the carbonization conduction or temperature, granulometric distribution and humidity of the analyzed charcoal, as well as the wood used as raw material.…”
Section: Charcoal Qualitycontrasting
confidence: 82%
See 3 more Smart Citations